Lessons learned from community and citizen science monitoring on the Elwha River restoration project - Eitzel, M. V.; Meyer, Ryan; Morley, Sarah; Miller, Ian; Shafroth, Patrick B.; Behymer, Chelsea; Jadallah, Christopher; Parks, David; Kagley, Anna; Shaffer, Anne; Ballard, Heidi (Frontiers in Ecology and Evolution, 2023)
Community and citizen science (CCS) projects - initiatives that involve public participation in scientific research - can both sustain and expand long-term monitoring of large dam removal projects. In this article, we discuss our perspectives on CCS associated with the Elwha River dam removals. We summarize how the public has been or could be involved in monitoring and distill lessons learned for other large dam removal projects. Much of the Elwha monitoring involved technical field work requiring training and incurring potential liability risks, guiding projects towards smaller-scale public involvement. Partnering with organizations that have capacity for volunteer management expanded CCS opportunities and provided logistical support to project managers committed to public engagement. We found that many projects engaged with students and/or with paid or unpaid interns; compensating participants in various ways can help to create reciprocal relationships that support long-term monitoring. In the future, other large dam removals could consider planning ahead for community involvement in dam removal monitoring to accommodate the technical and potentially hazardous nature of the work – broadening who may be able to participate. In addition, involving community members in setting research agendas could be an important first step in engaging them in long-term monitoring, in turn facilitating multi-generational research at the timescale of landscape-level changes. Finally, explicit relationship-building with Indigenous communities can enhance the benefits of community engagement in dam removal science for all involved.